Brothers or Stepbrothers?: Christianized Targum Manuscripts in the Sephardic Text Family - Tanja, Johanna M. (Aramaic studies, 2012)
Half of the textual witnesses of the Sephardic text group of Targum Samuel are of Christian origin, two manuscripts and two editions. This leads to two questions: How did a typically Jewish text like the Targum end up in the accepted corpus of Christian Biblical Studies in sixteenth century Spain? And how did it function?